Development of a project management methodology for use in a university-industry collaborative research environment - Chin, Christina May May (2012)
This study examines the growth, need for and demands on university-industry collaborative (UIC) partnerships as a vehicle for the nation‟s development through technological innovation. In Malaysia, gaps and weaknesses exist when compared to best practices, these limit the establishment and overall effectiveness of UICs. In the Malaysian context, UICs are by no means a new phenomenon, however the approaches adopted, the success stories and related issues have not received significant academic attention. Thus, this study aims to provide an insight into collaborative endeavours in Malaysia. This study adopted an exploratory interpretative case study approach via semi-structured interviews and self-administered questionnaire survey to collect data from university researchers, industry players and research agencies. This data, along with the findings from an extensive literature review were used to benchmark best practices and define the requirements that are placed on a PMM designed specifically for use in the Malaysian UIC project environment. Based on this analysis, a novel and appropriate PMM was developed and subsequently evaluated by an expert panel and iteratively refined. The primary outcome of this study is a PMM guidebook for use in the initiation, planning, execution, monitoring and closing of UIC research projects. The PMM developed aims to make project management best practices accessible and appropriate for the needs of UIC researchers and also encourages academic researchers to embrace project management knowledge which in turn helps them to understand industrial needs and wants. The PMM developed is customisable for project size and nature. It consists of a set of processes, templates, tools and techniques to assist in the planning and management of the project throughout the entire life cycle. The components of the PMM are (1) project management processes such as initiating, planning, executing and monitoring project progress with (2) a selection of tools and techniques to communicate delivery to the satisfaction of all stakeholders; (3) consolidated and integrated set of appropriate best practices and values of project management and (4) a list of references of terminology as a common denominator and language for us in the project environment.